Time, emergences and communications - Dugue, Bernard (Science, society and new technologies series, 2018)
This book presents an attempt to understand emergences in various situations where material components interact by coordinating their actions to "make system" with emerging properties (or functions) accessible to experimental investigation. So the strategy consolidates as much as possible the physical foundations and the understanding of the primordial matter and then passing to the realities based on very large numbers of elementary components.